(untitled) (Research, Society and Development, 2024)
Introduction: Pain management in children with cancer is a crucial concern in clinical practice, demanding a scientific and personalized approach. This article examines the available evidence on opioid administration in children, focusing on pediatric cancer cases. We seek to understand the inherent challenges and identify strategies to improve the efficacy and safety of this therapy in a vulnerable population. Methodology: We carried out an integrative review to analyze publications in Portuguese and English, from 2003 to 2023, excluding literature reviews. The data was summarized descriptively and recorded in tables to provide a comprehensive view of the available evidence on the topic. Discussion and Results: The review highlighted the need for personalized approaches, considering pharmacokinetic and pharmacodynamic variations in neonates and children. Undertreatment of pain, particularly in neonatal units, has highlighted the importance of overcoming educational barriers and implementing clear protocols. Analysis of plasma concentrations indicated the complexity in choosing administration strategies, with suggestions for combining basal infusion and intermittent bolus to optimize stability. Furthermore, sedation research has emphasized efficacy but also the need for caution, while nighttime care challenges have highlighted logistical obstacles. Taken together, the importance of a multifaceted approach, educational programs and family coping strategies for effective pain management in children with cancer is highlighted. Conclusion: This study highlights the complexity of opioid administration in children with cancer, emphasizing the importance of a personalized approach, educational programs, and strategies to address specific challenges, providing effective pain management throughout the pediatric cancer patient journey.